Catheter Ablation as a Treatment for Vasovagal Syncope: Long‐Term Outcome of Endocardial Autonomic Modification of the Left Atrium. Issue 7 (July 2016) - Sun, Wei; Zheng, Lihui; Qiao, Yu; Shi, Rui; Hou, Bingbo; Wu, Lingmin; Guo, Jinrui; Zhang, Shu; Yao, Yan
Abstract : Background: Autonomic modification through catheter ablation of ganglionated plexi (GPs) in the left atrium has been reported previously as a treatment for vasovagal syncope. This study aimed to observe the long‐term outcome in a larger cohort. Methods and Results: A total of 57 consecutive patients (aged 43.2±13.4 years; 35 women) with refractory vasovagal syncope were enrolled, and high‐frequency stimulation and anatomically guided GP ablation were performed in 10 and 47 cases, respectively. A total of 127 GP sites with positive vagal response were successfully elicited and ablated, including 52 left superior, 19 left lateral, 18 left inferior, 27 right anterior, and 11 right inferior GPs. During follow‐up of 36.4±22.2 months (range 12–102 months), 52 patients (91.2%) remained free from syncope. Prodromes recurred in 16 patients. No statistical differences were found between the high‐frequency stimulation and anatomically guided ablation groups in either freedom from syncope (100% versus 89.4%, P =0.348) or recurrent prodromes (50% versus 76.6%, P =0.167). The deceleration capacity, heart rate, and heart rate variability measurements demonstrated a reduced vagal tone lasting for at least 12 months after the procedure, with improved tolerance of repeated head‐up tilt testing. No complications were observed except for transient sinus tachycardia that occurred in 1 patient. Conclusions: Left atrial GP ablation showed excellent long‐term clinical outcomes and might be considered as a therapeutic option for patients with symptomatic vasovagal syncope.